HUMAN DEVELOPMENT IN KARNATAKA- HDI AND EDUCATION - Gowda B S, Krishne; Kumar, P. Hari (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Any country in the world without Human Development index like education, knowledge, skill, long living, income, health, standard of living, efficiency and caliber etc., it is not possible to develop any sector and GDP and economy of concern country. Particularly in developing and under developed countries, it is essential and inevitable to concentrate at maximum extent in the human development index. For the innovation and discovery of technology in any field the human skills, their education, their ability and efficiency are potential elements which plays a significant role. Therefore is necessary to know the human development progress updated by time to time. With this objective this study has taken with the objectives of identifying the human development index in Karnataka in terms of income, education, health and standard of living etc. For this purpose the secondary data has been collected and analysed and presented in the tables with the help of statistical tools like ratios, percentages CAGRs etc., and given the interpretation. The available data has been collected from secondary sources like journals, books, magazines, and concern annual reports etc.